Features of Prosthetics in Elderly People - Sadigov O.M.; Babayev E.E; Akhundov Y.H. (American Journal of Biomedicine and Pharmacy, 2025)
This article focuses on the role and significance of prosthetics for elderly individuals, exploring the specific challenges and considerations involved in prosthetic care for the aging population. As individuals age, changes in body structure, bone density, and skin elasticity impact the design and functionality of prosthetic devices. This study examines the use of prosthetics in elderly people, discussing their practical application and adaptability to age-related physiological changes. Additionally, the article explores the potential benefits of modern technologies, such as 3D printing and smart prosthetics, in enhancing the comfort and effectiveness of prosthetic solutions for older adults. The research highlights key factors that need attention when selecting prosthetics, including comfort, long-term usability, and the need for restored physical activity. The findings of this research will contribute to the development of new design directions and technological advancements in prosthetics aimed at improving the quality of life for the elderly population.